(untitled) (Papeles, 2024)
This work dialogues with studies related to state repressive violence, as it aims to address some aspects of the state of exception prior to the Uruguayan civil-military dictatorship that began in 1973; through the study of legislation and the use of theoretical foundations and repressive instruments applied by the State between 1968 and 1972.